Presencia saboyana en la corte de los paleólogos (1326-1347) - Garcés Ávalos, Galo (2015)
The purpose of the present article is to analyze the aspects of the presence of Savoyard courtiers in Byzantium after the wedding of Andronikos III Palaiologos with the princess Giovanna of Savoy, known by the Greeks as Anna of Lombardy, who had a decisive role in the Empire after the her husband’s demise in 1341, and who confronted John VI Kantakouzenos in the conflict known as the Second Byzantine Civil War (1341-1347), where she not only relied on the Byzantine noblemen loyal to her son, John V, but also on her Savoyard countrymen.